Analysis of ischemic stroke burden in Asia from 1990 to 2019: based on the global burden of disease 2019 data - Zhang, Xueli; Lv, Hengliang; Chen, Xin; Li, Maoxuan; Zhou, Xiaojing; Jia, Xiaoying (Frontiers in Neurology, 2023)
Background Ischemic stroke has the characteristics of high morbidity, mortality, and recurrence rate. This study aimed to describe and assess the burden of ischemic stroke in Asia based on the global burden of disease (GBD) 2019 data and provide a crucial scientific foundation for the prevention and control of this life-threatening disease. Method This study used the GBD 2019 data to assess the burden of ischemic stroke. The indicators used in this study were derived from the following methods: (i) the incidence of ischemic stroke was estimated using the disability model for the global burden of disease study-mixed effects regression (DisMod-MR), a Bayesian meta-regression disease modeling tool; (ii) the non-specific codes of all available data on mortality were corrected and used to estimate mortality rates for ischemic stroke and the cause of death ensemble model was used to estimate mortality rates; and (iii) the disability-adjusted life years (DALYs) is the sum of years lived with disability (YLD) and the years of life lost (YLL), which quantifies the health loss due to specific diseases and injuries. In addition, the joinpoint regression model was adopted to analyze the temporal trend of ischemic stroke from 1990 to 2019 in Asia. Result This study found an increase in the burden of ischemic stroke in 2019 compared to 1990. Moreover, the age-standardized incidence rate (ASIR) of ischemic stroke showed a gradual upward trend over the specific period. The age-standardized mortality rate (ASMR) showed a downward trend in Asia from 1990 to 2019. The burden of ischemic stroke was more concentrated on older age groups, particularly those older than 65 years. East Asia had the highest burden of ischemic stroke compared to other regions in Asia. Particularly, China, India, Indonesia, and Japan had the highest burdens of ischemic stroke among the Asian countries and regions. However, the population with the highest burden of ischemic stroke was still the elderly group. Conclusion Based on our study, it is evident that the burden of ischemic stroke exists substantially and exhibits variations in the aspects of age, gender, and geographical region in Asia. Without targeted implementation of population-wide primary strategies for prevention and control, the burden of ischemic stroke is likely to worsen significantly in the future.